Editorial: International Entrepreneurial Orientation - Krzysztof Wach (Entrepreneurial Business and Economics Review, 2015)
In recent decades, both the theory of internationalisation of the firm and/or the theory of international business have developed. Recent developments in international business studies prove that entrepreneurial orientation (EO) emerges as one of the important potential factors contributing to the intensification of the processes of internationalisation of the firm (Etemad, 2015; Gupta & Gupta, 2015). It seems that international entrepreneurship (IE) has been flourishing. The general theory of entrepreneurship indicates that market opportunities are a common and dominant link for all entrepreneurial activities. The entrepreneurship theory refers to the identification or creation opportunities, their evaluation and exploitation. The expansion into new geographic markets is undoubtedly an important market opportunity for growth and development. The internationalisation as a response to the market opportunity takes diverse paths. Based on the in-depth literature search, this issue of our journal aims to determine whether, why and how, in the context of diverse environmental conditions, the pursuit of market opportunities contributes to the increase of internationalisation of the firm (Dimitratos & Plakoyiannaki, 2003; Dimitratos, Voudouris, Plakoyiannaki & Nakos,. 2012; Wach. 2015).